Analysis of Microtremor Data for Identification of Sediment Layer Thickness Based on Ground Profile Vs in Solok City, West Sumatera - Cahya Damayanti (Department of Physics, Sebelas Maret University, 2023)
Research has been carried out to analyze the thickness of the sediment layer based on the value of the ground profile Vs (S-wave velocity) from microtremor measurement data sources in Solok City. The thickness of the sediment layer is one of the parameters that affect the amplification or amplification of incoming waves when an earthquake occurs. This study aimed to determine the sediment thickness level in Solok City based on the Vs value in the ground profile model from microtremor data sources. So that the analysis of sediment layers can be used as a form of disaster mitigation caused by tectonic activities such as earthquakes. Single station and array microtremor data were collected, then processed using a combination of HVSR and SPAC methods. The data processing results indicate that the value of S-wave velocity (Vs) derived from microtremor data analysis can be used to determine the thickness of the sediment layer (h), and vs values in Solok City ranged from 126.15-193.35 m/s with depths between 7.23-19.06 m. For areas with unseparated volcanic rock (QTau) lithology, the Vs value is 182.41 m/s. Meanwhile, for areas with geological conditions like alluvium (Qal), the Vs value is 161.66 m/s. The area with a thick layer of sediment, which is 62.74 m, is in the center of the northeastern part of Solok City, covering most of Vi Suku, Nan Balimo, and Javanese Village with alluvium (Qal) lithology and low topography through which rivers flow. Meanwhile, the thin layer of sediment, which is 23.12 m, is located in the western part of Solok City, precisely in Tanah Garam, with undivided volcanic rock lithology (QTau) and high topography in hilly areas.